QUIZIZZ APLICATION AS THE BRIDGING EVALUATION ON ENGLISH GRAMMAR MATERIAL OF ESP STUDENTS - Rahayu, Yoni; Aprianti, Iis; Sulaiman, Eugelin (Universitas Muhammadiyah Tapanuli Selatan, 2023)
This study aims to know the ESP students’ perception in applying Quizizz application for evaluation on English Grammar material. This research used Applied Research based on information technology where Quizizz is used as an evaluation tool. The subjects of the research were 81 students from the second semester of Management Study Program of University of Timor. The researcher used test and questionnaire to gain the data of the research. The test consisted of 15 questions relating to grammar material (Pronoun, Passive voice, and Modality). The test was multiple choice question form. Then, the researcher created questionnaire to find out the students’ perception or responses about using Quizizz application as the evaluation tool. The research findings shows that there were positive perspectives of the students toward applying Quizizz. It was as the results of students’ score in Quizizz and their final exams. There were improvement in their final test. In conclusion, the students regarded that Quizizz is attractive game consisted of live top chart, music. The students can know the correct answers and enjoy to answer the questions in this application.